Relations between economic zoobenthos species and ecological characteristics of Thi Nai lagoon, Vietnam - Ngai, Phan Duc; Tuan, Vo Si (Vietnam Journal of Marine Science and Technology, 2019)
Relations between economic zoobenthos species and ecological characteristics of Thi Nai lagoon were reported as results of three surveys carried out during 2014–2015. The results have pointed out 11 zoobenthos species that have primarily economic value at the Thi Nai lagoon (5 bivalve species, 5 crustacea species and 1 gastropoda species). Bivalve group possesses 91% of the entire commercial yield of benthic animal (7,456.9 tons/year), in which Glauconome chinensis and Gari elongata possess dominatingly (possess 90% of the entire commercial yield of bivalves: 6,817 tons/year). Bivalve and gastropoda groups were found in correlation with sandy sediment and mangroves but crustacea group was found in correlation with muddy sand sediments and seagrass. The results of this study will conntribute the scientific basis for further studies on the trophic relationship, food web and data for planning, zoning and appropriate exploitation of fisheries resources.